2019
DOI: 10.3390/cells9010094
|View full text |Cite
|
Sign up to set email alerts
|

Host Calcium Channels and Pumps in Viral Infections

Abstract: Ca2+ is essential for virus entry, viral gene replication, virion maturation, and release. The alteration of host cells Ca2+ homeostasis is one of the strategies that viruses use to modulate host cells signal transduction mechanisms in their favor. Host calcium-permeable channels and pumps (including voltage-gated calcium channels, store-operated channels, receptor-operated channels, transient receptor potential ion channels, and Ca2+-ATPase) mediate Ca2+ across the plasma membrane or subcellular organelles, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
121
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(127 citation statements)
references
References 73 publications
4
121
0
2
Order By: Relevance
“…The nding suggested that hypocalcemia might be the early warning factor for the trend of critical illness in patients with COVID-19. A recent review about Ca 2+ and virus infection explained that during the process of virus infection, the virus uses the host cell's environment to replicate and induce host cell dysfunction by capturing the calcium signal system in the host cell [14]. Due to the hijack of Ca 2+ system of the host's cells, the virus can inhibit T-cell reactivity, anti-apoptosis, and other functions and affect the occurrence and progression of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The nding suggested that hypocalcemia might be the early warning factor for the trend of critical illness in patients with COVID-19. A recent review about Ca 2+ and virus infection explained that during the process of virus infection, the virus uses the host cell's environment to replicate and induce host cell dysfunction by capturing the calcium signal system in the host cell [14]. Due to the hijack of Ca 2+ system of the host's cells, the virus can inhibit T-cell reactivity, anti-apoptosis, and other functions and affect the occurrence and progression of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Both Ca 2+ homeostasis and ROS production are widely proven to play important roles in defense against invading pathogens and prevent their further proliferation in cells (Flury et al, 2013; Chen et al, 2019). If these known host defense responses have been shut down by βC1, then we would expect that host resistance against the begomovirus is compromised.…”
Section: Resultsmentioning
confidence: 99%
“…One of the facilitators of cellular entry of viruses is ion channels, which are utilized during the initial stages of infection. Ion channels are cellular proteins that facilitate the movement of ions across the cell membrane into and out of the cells [ 24 ]. This movement of ions across the channels changes electrical signals across the cell membrane and, as a result, rapid changes occur, causing changes in the intensity of intracellular messengers that regulate various cellular roles.…”
Section: Discussionmentioning
confidence: 99%